2003
DOI: 10.1093/jn/133.11.3630
|View full text |Cite
|
Sign up to set email alerts
|

Geographical, Seasonal and Gender Differences in Folate Status among Chinese Adults

Abstract: Low blood folate concentrations have been associated with cardiovascular disease, neural tube defects and selected cancers, but little is known about folate status in Chinese adults. In a cross-sectional study we measured the plasma and red blood cell folate concentrations in 2422 Chinese men and women aged 35 to 64 y, living in the North and South of China, who provided blood samples either in March or September of 2001. The geometric mean concentrations of plasma and red blood cell folate were lower among No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 25 publications
8
105
1
Order By: Relevance
“…Nevertheless, the close agreement between the actual and predicted decline in NTD rates in countries with mandatory folic acid fortification suggests the equation is valid (29) for predicting change in NTD rate with a change in population folate status. Furthermore, the finding of lower blood folate concentrations and higher NTD rates in northern v. southern China suggests that this relationship applies in an Asian setting (8) .…”
Section: Resultsmentioning
confidence: 98%
“…Nevertheless, the close agreement between the actual and predicted decline in NTD rates in countries with mandatory folic acid fortification suggests the equation is valid (29) for predicting change in NTD rate with a change in population folate status. Furthermore, the finding of lower blood folate concentrations and higher NTD rates in northern v. southern China suggests that this relationship applies in an Asian setting (8) .…”
Section: Resultsmentioning
confidence: 98%
“…Some studies have reported that folate deficiency is fairly common in many Chinese areas, especially northern China including Beijing [40][41][42][43]. In Taixing city, the present study field area, located in the Northern Jiangsu province, the boundary between North and South China, most residents are country people with low consumption of fresh vegetables and fruits due to the relative low economic level.…”
Section: Discussionmentioning
confidence: 99%
“…Until today, there is no evidence of studies that have calculated the health impact of folate deficiency at population level (see section 2.2). Given that Northern China (Hao et al, 2003; see also Figure 7), and Shanxi Province in particular , has one of the highest folate deficiency rates in the world, there is a need to estimate the current burden of this micronutritional disease at regional/provincial level.…”
Section: Rq4mentioning
confidence: 99%
“…However, evidence on the total number of folate deficient people in China is scarce (WHO, 2009a;Micronutrient Initiative, 2011b). Only two studies reported the folate deficiency rate in Chinese regions, spread across the country (Hao et al, 2003;Zhao et al, 2009). Other folate status and intake assessment studies in China focused on specific regions, characterized by a low NTD prevalence rate, such as in Shanghai (Shrubsole et al, 2001), Jiangsu (Li et al, 1996;Ren et al, 2007) and Anqing (Ronnenberg et al, 2000), or a high prevalence of NTDs, for instance in Shanxi (Li et al, 1996;Zhang et al, 2006;Ren et al, 2007;Zhang et al, 2008) and Beijng (Gao et al, 2003).…”
Section: Folate Deficiency In Chinamentioning
confidence: 99%
See 1 more Smart Citation